ROMANTISME LIRIK LAGU DALAM ALBUM YANG TERPILIH DAN HARMONI JALINAN NADA DAN CERITA KARYA ROSSA - Mia Indriyani Indriyani; Elmustian Rahman Rahman; Hadi Rumadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research based on literature. The Issues discussed is romanticism in song lyrics by Rossa. Assessment on the element of romanticism is irresistible study. A literature that tells of an event difficult released from the flow of romanticism. Romanticism was description or delineation of which give priority to the feeling was expressed through the event of affection, sacrifice, suffering, and happiness. The problems that interested the author of the analysis that is how is the romanticism that expresses compassion, sacrific, suffering, excitement Rossa song lyrics by using a method of descriptive. A source of data on this research is chosen album of Yang Terpilih and Harmoni Jalinan Nada dan Cerita by rossa. This research data of sentences that contain romanticism in song lyrics. Data collection of this research with engineering documentation or literature, the technique of reading, the technique of note, and techniques of identification. The data is then analyzed through technique descriptive qualitative analysis of each sentence is a load of romanticism found in song lyrics by rossa to be shown and reinforced with evidence. Of the two albums, there are 3 song is express romantic affection, 10 song that expresses the sacrifice of romanticism, 12 song which expresses the romanticism of suffering, and 5 song that express romantic excitement. Keyword: romanticism, lyric, song, Rossa